Acute Coronary Syndrome (ACS) during Corona Virus Disease-19 (COVID-19) Pandemic: A Single-Center Comparative Study - Dibya K. Baruah; Anuradha Darimireddi; Ravikanth Telikicherla; Suresh Allamsetty (Assam Journal of Internal Medicine)
Aim: To analyze the impact of corona virus disease-19 (COVID-19) pandemic and various containment measures taken for the pandemic control on hospital admissions of acute coronary syndrome (ACS). Materials and Methods: This study is a single-center, comparative study conducted at a tertiary care center situated in the southern part of India. The study period was from March 1, 2020 till May 31, 2020, including the first lockdown period in India. All patients admitted with a diagnosis of ACS to our hospital during the study period were included in the study (study group). This group was compared with the patients admitted with ACS into our hospital during the corresponding period of the previous year (control group). Patients with ST-elevation myocardial infarction (STEMI) were compared with the control group for clinical profile, treatment, hospital course, outcome, and incidence rate ratio (IRR) of admissions. Results: There was a significant reduction of mean daily admissions of ACS cases in the study group with IRR of 0.702; 95% confidence interval (CI), 0.719–1.02; P < 0.001. The reduction rate of ACS cases was 29.74% (study period, n = 215; control period, n = 306), and it was mostly related to a decline in the number of non-ST-elevation myocardial infarction (NSTEMI) and unstable angina. No significant reduction of patients with STEMI was observed between the groups. However, patients with STEMI had more left ventricular (LV) dysfunction, LV thrombus, and a significantly higher incidence of mitral regurgitation (13.3% vs. 8.8%, P < 0.05). The impact of the COVID-19 outbreak on the patients with ACS revealed a parallel reduction of hospital admissions with an increasing number of COVID-19 cases in the community. Conclusion: The COVID-19 pandemic and concomitant social restrictions resulted in a significant decline in hospital admissions due to ACS in this tertiary care center, but without any effect on the number of admissions with STEMI. A parallel reduction of hospital admissions for ACS cases with a rising number of COVID-19 cases in the community was also observed in this study.